Lipoprotein-Associated Phospholipase A2 Mass Level Is Increased in Elderly Subjects with Type 2 Diabetes Mellitus - J. Fortunato; V. Bláha; J. Bis; J. Št’ásek; C. Andrýs; J. Vojáček; B. Jurašková; L. Sobotka; P. Polanský; M. Brtko (Journal of Diabetes Research)
Objective. Lipoprotein-associated phospholipase A2 (Lp-PLA2) is extensively expressed by advanced atherosclerotic lesions and may play a role in plaque instability. We selected a group of elderly subjects that underwent transcatheter aortic valve implantation (TAVI) or balloon angioplasty (BA) and separated them into two groups, diabetic and nondiabetic, to compare the level of Lp-PLA2 mass between them. Methods. 44 patients aged 79.6±5.6 years with symptomatic severe aortic valve stenosis underwent TAVI (n=35) or BA (n=9). 21 subjects had confirmed type 2 diabetes mellitus. Lp-PLA2 mass was measured using an enzyme-linked immunosorbent assay kit (USCN Life Science, China) before and 3 days after the procedure. Results. Lp-PLA2 mass was significantly elevated in this population (1296±358 ng/mL before TAVI; 1413±268 ng/mL before BA) and further increased after TAVI (1604±437 ng/mL, P<0.01) or BA (1808±303 ng/mL, P<0.01). Lp-PLA2 mass was significantly increased on the diabetic group before these interventions. Conclusion. Lp-PLA2 may be a novel biomarker for the presence of rupture-prone atherosclerotic lesions in elderly patients. Levels of Lp-PLA2 in diabetic patients may accompany the higher amount of small dense LDL particles seen in these subjects.